Bioinformatics Analysis of Inhibition Activation SHP-2 by Galangal as Activating Agent of Cancer Immunotherapy - Ardriyanto, Maria Indra; Rahman, Faaza Aulia; Hastuti, Hanaan Emilia Adi; Meiyanto, Edy; Kawai, Taro; Putri, Dyaningtyas Dewi Pamungkas (Indonesian Society for Cancer Chemoprevention, 2023)
Interleukin 12 (IL-12) is a pro-inflammatory cytokine type 1 that has acted as a potential immunotherapy for cancer. The mechanism of IL-12 increases the activity of cytotoxic T cells and Natural Killer (NK) cells, reverse tumor-induced immunosuppression, prevent angiogenesis, and increases lymphocyte and antigen transport. Galangal is one of the natural ingredients that have biological activity as an anticancer and immunomodulator. In this research, researchers wanted to know the potential of the active compound of galangal to activate IL-12 by inhibiting the IL-12 analog, namely SHP-2. This research uses bioinformatics studies using several databases such as RCSB PDB, ChEMBL, Dr. Duke's Phytochemical and Ethnobotanical, UALCAN, OncoLnc and computational analysis using KNIME and MOE software. The SHP-2 structure used is taken from the RCSB PDB with the code 5EHR. The 10 compounds with the highest predictions of inhibiting SHP2 using KNIME were obtained, then molecular docking was performed using MOE and three compounds that had the potential to inhibit SHP-2 were Kaempferide, Galangin, and RiboflavinKeywords: cancer, computing, galangal, Interleukin 12, SHP-2.